Handbook for Philippine museums - Peralta, Jesus T. 1932- (National Commission for Culture and Arts, NCCA Committee of Museums, 1993)
Purpose: A reference guide "for museum workers in the Philippines." : "prepared for the use of small museums with limited conservation facilities to enable the curator to confront daily problems, and to institute emergency measures."